Identification of Simultaneous Occurrence of Amphibian Chytrid Fungi and Ranavirus in South Korea - Ji-Eun Lee; Young Jin Park; Mun-Gyeong Kwon; Yun-Kyeong Oh; Min Sun Kim; Yuno Do (Animals)
Emerging infectious diseases such as chytridiomycosis and ranavirosis, caused by Batrachochytrium dendrobatidis (Bd) and ranavirus (RV), respectively, are major contributors to global amphibian declines. Despite their significance, comprehensive data on the spatial epidemiology of these pathogens in South Korea remain limited. This study aimed to assess the nationwide co-occurrence and prevalence of Bd and RV across four anuran species in five administrative regions. Infection rates were analyzed in relation to host species, sex, and life history stage. Results indicated distinct prevalence patterns driven by ecological traits. Bd was predominantly detected in mountainous and coastal habitats, whereas RV was more common in flat inland areas. Both pathogens exhibited peak occurrence in central regions, likely reflecting seasonal transmission dynamics rather than stable endemic hotspots. The observed spatial heterogeneity appears to be influenced by pathogen-specific thermal tolerance and host ecology. These findings underscore the importance of understanding host–pathogen–environment interactions for effective disease surveillance and management. Continuous monitoring and integrative ecological approaches are essential to mitigate pathogen-induced biodiversity loss and to inform amphibian conservation strategies in East Asia.